Reticular film pasting material production process

By impregnating fluororesin mixed liquid A and liquid B on the glass fiber cloth, combined with high-temperature ink printing patterns and butyl glue backing glue, the existing wall decoration materials are easily faded and not stain-resistant outdoors, and the production process of mesh film patches with good weather resistance is achieved.

CN120326982APending Publication Date: 2025-07-18YANCAI NEW MATERIALS TECHNOLOGY (JIANGSU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510393927.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

Existing wall decorative materials such as PVC wallpaper, wall cloth and fiberglass wall cloth are prone to fading, not stain-resistant and have poor decorative properties when used outdoors, and cannot meet the application needs in harsh environments.

Method used

The mesh film patch production process is adopted, and the fluororesin mixed liquid A and liquid B are successively impregnated on the glass fiber cloth, combined with high-temperature ink printing patterns, and butyl glue is used as the backing glue to form a coating with good weather resistance.

Benefits of technology

The wall cloth made has good weather resistance in outdoor environments, and the printed patterns do not fade, which improves the wear resistance, stain resistance and water resistance of the coating, and has exquisite and diverse patterns and is resistant to ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of special textiles, high polymer materials and building materials, in particular to a reticular film pasting material production process which comprises the following steps: (1) mixing: preparing a mixed solution of two fluororesins; (2) dipping: dipping, blade-coating or spraying the fluororesin mixed solution A on one side of the glass fiber cloth; (3) drying: drying the impregnated glass fiber cloth; (4) texture printing: printing colored texture patterns on the membrane material by using high-temperature ink and a special texture machine; (5) drying the texture patterns; (6) impregnating, namely impregnating, blade-coating or spraying the fluororesin mixed solution B on one side of the glass fiber cloth; (7) drying; (8) slitting: slitting the membrane material into a certain specification by using an automatic membrane material slitting machine; and (9) packaging: packaging the membrane material by using an automatic packaging machine to obtain a finished product. The tensile strength, water resistance, stain resistance and aging resistance of common PVC decorative stickers such as wall cloth are improved, and the PVC decorative stickers have exquisite and diverse patterns, are good in weather resistance, resistant to ultraviolet rays and free of color fading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special textiles, polymer materials and building materials, and in particular to a production process of a mesh film pasting material. Background Art

[0002] Currently, most of the existing wall decoration materials are PVC wallpaper, wall cloth, wall panels, fiberglass wall cloth (Haiji cloth, stone cloth), etc. PVC materials have certain decorative properties, but they are not resistant to aging, easy to fade, not resistant to stains and do not meet standards, and cannot be used outdoors and in harsh environments. Fiberglass wall cloth has poor decorative properties and needs to be constructed with latex paint, and it also has no pattern effect.

[0003] CN101240509A discloses a method for manufacturing a polytetrafluoroethylene spatial structure architectural membrane material, which is made into an architectural membrane material by impregnating, drying and sintering glass fiber cloth. The architectural membrane material is applied to a structural roof, but is not stain-resistant enough.

[0004] Therefore, a new technical solution is needed to solve the above technical problems. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a wallpaper wall cloth, which can be used outdoors, is resistant to aging, not easy to fade, has a standard stain resistance, and is a decorative glass fiber wall cloth.

[0006] In order to solve the above technical problems, the present invention provides a mesh film material production process, comprising the following steps: (I) Mixing: preparing fluororesin mixed liquid A and fluororesin mixed liquid B; The fluororesin mixed liquid A has the following proportions: 30-80% fluororesin, 1-5% titanium dioxide, 0.1-0.5% penetrant, 1-8% thickener, 0.1-0.5% wetting agent, 0.1-1% silane coupling agent, 5.5%-65.8% deionized water, mixed evenly, with a viscosity of 30-110 ku; The fluororesin mixed liquid B has the following proportions: 30-85% fluororesin, 1-3% thickener, 0.1-0.5% wetting agent, 0.1-1% silane coupling agent, 11.5%-69.8% deionized water, mixed evenly, with a viscosity of 30-110 ku; (ii) Impregnation: Impregnate, scrape or spray the fluororesin mixed liquid A on one side of the glass fiber cloth once or multiple times, and dry it at 370-390 degrees to form a uniform and smooth surface coating; the impregnation, scraping or spraying speed is 0.5m-5m / min; (iii) Texture printing: The desired design pattern is printed on the surface of the heated and dried coating using high temperature ink, and then dried at a temperature of 200-300 degrees; (4) Impregnation: Once or multiple times impregnate, scrape coat or spray fluororesin mixed solution B on the surface layer of the dried printed pattern in a single side, and then dry it by heating at 370 - 390 °C to form a uniform, smooth and transparent surface coating. The impregnation, scraping coat or spraying speed is 0.5 m - 5 m / min; (5) Slitting, cutting, and packaging.

[0007] By adopting the above technical solution, first impregnate, scrape coat or spray dry the fiberglass cloth with fluororesin mixed solution A in a single side, after texture printing treatment, then conduct the second impregnation, scraping coat or spraying of fluororesin mixed solution B in a single side. The made wall cloth can be applied outdoors, has good weather resistance, and ensures that the printed pattern does not fade, improving the wear resistance, stain resistance and waterproofness of the fiberglass cloth coating.

[0008] Adding coupling agent and titanium dioxide in the fluororesin mixed solution A strengthens the adhesion between the high-temperature ink and the base coating, the pattern clarity and the ink absorption rate. The mixed fluororesin mixed solution B is transparent, increasing the wear resistance, waterproofness and stain resistance of the coating.

[0009] Preferably, the thickness of the fiberglass cloth is 0.05 - 0.6 mm.

[0010] Preferably, on the back of the fiberglass cloth that has not been impregnated, scrape coated or sprayed with fluororesin mixed solution A and B for once or multiple times, back glue butyl rubber by hot melt extrusion method, with a thickness of 0.3 - 2 mm and a hot melt temperature of 100 - 120 °C.

[0011] By adopting the above technical solution, the back glued butyl rubber has the waterproof function without re-coating and pasting.

[0012] Preferably, a centrifugal film is attached when the butyl rubber is cooled.

[0013] Preferably, the thickness of the centrifugal film is 0.3 - 2 mm.

[0014] By adopting the above technical solution, the centrifugal film acts as an isolation film to prevent sticking.

[0015] Preferably, the components of the fluororesin mixed solution A further include hindered phenol antioxidants with a mass ratio of 0.1 - 1%.

[0016] By adopting the above technical solution, it effectively neutralizes the peroxide free radicals in the coating and improves the weather resistance of the fluororesin mixed solution A.

[0017] Preferably, the components of the fluororesin mixed solution B further include benzophenones with a mass ratio of 0.1 - 0.5%.

[0018] By adopting the above technical solution, the fluororesin mixed with benzophenones can effectively absorb ultraviolet rays in the 280 - 380 nm wavelength band, avoiding photo-oxidative degradation of the coating.

[0019] The present invention has the following beneficial effects compared with the prior art: 1. In the present invention, the glass fiber cloth is first impregnated, scraped or sprayed on one side with the fluororesin mixed A liquid and dried, then subjected to texture printing treatment, and then impregnated, scraped or sprayed on one side with the fluororesin mixed B liquid for the second time. The made wall cloth can be applied outdoors and in harsh environments, has good weather resistance, ensures that the printed pattern does not fade, and improves the wear resistance, stain resistance and waterproofness of the glass fiber cloth coating.

[0020] 2. The present invention uses a glass fiber as the base cloth, coats a polytetrafluoroethylene high-temperature resistant coating, and prints a high-temperature resistant ink pattern, which improves the tensile strength, fire resistance, waterproofness, stain resistance and aging resistance of ordinary PVC decorative materials (such as wall cloth and wall panels). Printing high-temperature resistant ink makes it have delicate and diverse patterns and is resistant to ultraviolet rays and does not fade.

[0021] 3. In the present invention, a coupling agent and titanium dioxide are added to the fluororesin mixed A liquid, which strengthens the adhesion between the high-temperature resistant ink and the base coating, the pattern clarity and the ink absorption rate. The back glue butyl rubber strengthens the waterproof effect on the base layer. Specific implementation mode General embodiment

[0022] The production process of the net-shaped film material is characterized by including the following steps: (1) Mixing materials: Prepare the fluororesin mixed A liquid and the fluororesin mixed B liquid according to the mass ratio; The component ratio of the fluororesin mixed A liquid is as follows: 30 - 80% of fluororesin, 1 - 5% of titanium dioxide, 0.1 - 0.5% of penetrant, 1 - 8% of thickener, 0.1 - 0.5% of wetting agent, 0.1 - 1% of silane coupling agent, 5.5% - 65.8% of deionized water, mix evenly, and the viscosity is 30 - 110 ku. The components of the fluororesin mixed A liquid also include 0.1 - 1% of hindered phenol antioxidants, and the hindered phenol antioxidant is Irganox 1010, which effectively neutralizes the peroxide radicals in the coating and improves the weather resistance of the fluororesin mixed A liquid.

[0023] The component ratio of the fluororesin mixed B liquid is as follows: 30 - 85% of fluororesin, 1 - 3% of thickener, 0.1 - 0.5% of wetting agent, 0.1 - 1% of silane coupling agent, 11.5% - 69.8% of deionized water, mix evenly, and the viscosity is 30 - 110 ku. The components of the fluororesin mixed B liquid also include 0.1 - 0.5% of benzophenone, and the benzophenone is UV - 531, which effectively absorbs ultraviolet rays in the 280 - 380 nm band and avoids photo - oxidative degradation of the coating.

[0024] (2) Impregnation: Impregnate, scrape, or spray the fluororesin mixture A solution on one side of the fiberglass cloth once or multiple times, and dry it at 370 - 390 degrees to form a uniform and smooth surface coating; the impregnation, scraping, or spraying speed is 0.5m - 5m / min; the thickness of the fiberglass cloth is 0.05 - 0.6mm.

[0025] (3) Texture printing: Use high-temperature ink to print the desired design pattern on the surface of the coating after heating and drying, and dry it at a temperature of 200 - 300 degrees. (4) Impregnation: Impregnate, scrape, or spray the fluororesin mixture B solution on one side of the surface of the dried printed pattern once or multiple times, and heat and dry it at 370 - 390 degrees to form a uniform, smooth, and transparent surface coating. The impregnation, scraping, or spraying speed is 0.5m - 5m / min. (5) Slitting, cutting, and packaging.

[0026] On the back of the fiberglass cloth that has not been impregnated, scraped, or sprayed with the fluororesin mixture A or B solution once or multiple times, apply butyl rubber by hot melt extrusion, with a thickness of 0.3 - 2mm and a hot melt temperature of 100 - 120 degrees. After the butyl rubber is hot melted, it is cooled, and a centrifugal film is attached during cooling. The thickness of the centrifugal film is 0.3 - 2mm.

[0027] In this application, the fiberglass cloth is first impregnated, scraped, or sprayed with the fluororesin mixture A solution on one side, dried, subjected to texture printing, and then impregnated, scraped, or sprayed with the fluororesin mixture B solution on one side for the second time. The made wall cloth can be applied to the outdoor and harsh environments, has good weather resistance, ensures that the printed pattern does not fade, and improves the wear resistance, stain resistance, and waterproofness of the fiberglass cloth coating. Example 1

[0028] Select a fiber cloth with a thickness of 0.18 as the base cloth, and scrape the A solution on one side once. The component ratio of the A solution is: polytetrafluoroethylene 30%, titanium dioxide 1%, wetting agent 0.1%, penetrant 0.1%, silane coupling agent 0.2%, polyurethane thickener 2.5%, Irganox 1010 0.1%, deionized water 15.3%. After drying at 370 degrees, impregnate the A solution on one side again. The component ratio of the A solution is: polytetrafluoroethylene 40%, titanium dioxide 3%, wetting agent 0.2%, penetrant 0.2%, silane coupling agent 0.1%, polyurethane thickener 1%, Irganox 1010 0.2%, deionized water 14.9%. Spray high-temperature ink, and then scrape the B solution on one side twice. The component ratio of the B solution is: polytetrafluoroethylene 30%, wetting agent 0.1%, UV-531 0.1%, silane coupling agent 0.1%, deionized water 11.5%. After drying at 370 degrees, apply butyl rubber by hot melt extrusion on the back, with a thickness of 0.3mm and a hot melt temperature of 100 degrees. Attach a centrifugal film during cooling.

[0029] The film pattern obtained in this example is relatively clear. The adhesion between the coating and the base fabric is 0 grade according to the cross-cut method of GB / T9286. Example 2

[0030] Select a fiber cloth with a thickness of 0.09 as the base fabric, and scrape and coat liquid A once on one side. The component ratio of liquid A is: polytetrafluoroethylene 50%, titanium dioxide 3%, wetting agent 0.4%, penetrant 0.3%, silane coupling agent 0.2%, polyurethane thickener 2.5%, Irganox 1010 0.6%, deionized water 30%. After drying at 370 degrees, impregnate liquid A once on one side again. The component ratio of liquid A is: polytetrafluoroethylene 60%, titanium dioxide 4%, wetting agent 0.2%, penetrant 0.4%, silane coupling agent 0.2%, polyurethane thickener 2%, Irganox 1010 1%, deionized water 14.9%. Spray high-temperature ink, and then scrape and coat liquid B twice on one side. The component ratio of liquid B is: polytetrafluoroethylene 80%, wetting agent 0.4%, silane coupling agent 0.5%, polyurethane thickener 2%, deionized water 30%. After drying at 370 degrees, apply butyl rubber by hot melt extrusion on the back, with a thickness of 0.3 mm and a hot melt temperature of 115 degrees. Attach a centrifugal film during cooling.

[0031] The film pattern obtained in this example is clear. The adhesion between the coating and the base fabric is 1 grade according to the cross-cut method of GB / T9286. Example 3

[0032] Select a fiber cloth with a thickness of 0.18 as the base fabric, and scrape and coat liquid A twice on one side. The ratio of liquid A is: copolymer of tetrafluoroethylene and perfluoropropyl vinyl ether 80%, titanium dioxide 5%, wetting agent 0.5%, penetrant 0.5%, silane coupling agent 1%, polyurethane thickener 8%, Irganox 1010 1%, deionized water 65%. After drying at 370 degrees, spray high-temperature ink, and then scrape and coat liquid B once on one side. The ratio of liquid B is: polytetrafluoroethylene 85%, wetting agent 0.5%, silane coupling agent 1%, polyurethane thickener 3%, deionized water 69%. After drying at 390 degrees, apply butyl rubber by hot melt extrusion on the back, with a thickness of 0.3 mm and a hot melt temperature of 120 degrees. Attach a centrifugal film during cooling.

[0033] The film pattern obtained in this example is relatively clear. The adhesion between the coating and the base fabric is 1 grade according to the cross-cut method of GB / T9286.

[0034] Comparative Example 4: Select a fiber cloth with a thickness of 0.18 as the base cloth, and scrape the liquid A on one side twice. The component ratio of the liquid A is: polytetrafluoroethylene 81%, titanium dioxide 1%, wetting agent 0.5%, polyurethane thickener 2.5%, deionized water 15.0%. After drying at 370 degrees, roll-print high-temperature ink, and then impregnate the liquid B on one side once. The component ratio of the liquid B is: polytetrafluoroethylene 80%, wetting agent 0.5%, polyurethane thickener 1%, deionized water 18.5%. After drying at 390 degrees, back-adhere butyl rubber by means of hot melt extrusion on the back, with a thickness of 0.3 mm and a hot melt temperature of 116 degrees. Attach a centrifugal film during cooling.

[0035] The film pattern obtained in this example is blurred, and the adhesion between the coating and the base cloth is 3 levels according to the cross-cut method of GB / T9286.

[0036] The detection of some performance indicators of the film materials of each example is listed as follows:

[0037] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. The production process of the mesh film patch material is characterized in that: It includes the following steps: (1) Mixing: Prepare fluororesin mixed solution A and fluororesin mixed solution B according to the mass ratio; The composition ratio of the fluororesin mixed solution A is as follows: 30 - 80% of fluororesin type, 1 - 5% of titanium dioxide, 0.1 - 0.5% of penetrant, 1 - 8% of thickener, 0.1 - 0.5% of wetting agent, 0.1 - 1% of silane coupling agent, 5.5% - 65.8% of deionized water. Mix evenly, and the viscosity is 30 - 110 ku; The composition ratio of the fluororesin mixed solution B is as follows: 30 - 85% of fluororesin type, 1 - 3% of thickener, 0.1 - 0.5% of wetting agent, 0.1 - 1% of silane coupling agent, 11.5% - 69.8% of deionized water. Mix evenly, and the viscosity is 30 - 110 ku; (2) Impregnation: Impregnate, scrape, or spray the fluororesin mixed solution A on one side of the fiberglass cloth once or multiple times, and dry it at 370 - 390 °C to form a uniform and smooth surface coating; the impregnation, scraping, or spraying speed is 0.5 m - 5 m / min; (3) Texture printing: Use high-temperature ink to print the required design pattern on the surface of the coating after heating and drying, and dry it at a temperature of 200 - 300 °C; (4) Impregnation: Impregnate, scrape, or spray the fluororesin mixed solution B on one side of the surface of the dried printed pattern once or multiple times, and dry it at 370 - 390 °C by heating to form a uniform, smooth, and transparent surface coating. The impregnation, scraping, or spraying speed is 0.5 m - 5 m / min; (5) Slitting, cutting, and packaging.

2. The production process of the mesh film patch material according to claim 1, characterized in that: The thickness of the fiberglass cloth is 0.05 - 0.6 mm.

3. The production process of the mesh film patch material according to claim 1, characterized in that: On the back of the fiberglass cloth that has not been impregnated, scraped, or sprayed with the fluororesin mixed solution A and B once or multiple times, back glue butyl rubber by means of hot melt extrusion, with a thickness of 0.3 - 2 mm and a hot melt temperature of 100 - 120 °C.

4. The production process of the mesh film patch material according to claim 3, characterized in that: A centrifugal film is attached when the butyl rubber cools.

5. The production process of the mesh film sticker according to claim 4, characterized in that: The thickness of the centrifugal film is 0.3 - 2 mm.

6. The production process of the net-shaped film sticker material according to claim 1, characterized in that: The components of the fluororesin mixed solution A further include 0.1 - 1% of hindered phenol antioxidants by mass ratio.

7. The production process of the mesh film patch material according to claim 1, characterized in that: The components of the fluororesin mixed solution B further include 0.1 - 0.5% of benzophenones by mass ratio.

Citation Information

Patent Citations

  • Method for preparing polytetrafluoroethylene spatial structure building film material

    CN101240509A